Over-All Accuracy of 99mTc-Pertechnetate Brain Scanning for Brain Tumours – Study of 471 Patients - Björnsson, O.G.; Pétursson, E.; Sigurbjörnsson, B.; Davidsson, D. (Nuklearmedizin - NuclearMedicine, 1978)
A 3-year follow-up and re-evaluation of all scans on all patients referred for brain scanning in Iceland during 1 year was performed in order to assess the diagnostic reliability of radioisotope scanning for brain tumours. The study included 471 patients. Of these 25 had primary brain tumours and 7 brain metastases. Scans were positive and correctly interpreted in68 % of the patients with primary brain tumours and in 3 of the 7 patients with metastases. The over-all accuracy of brain scanning for brain tumours defined as the total number of correct positive scans and correct negative scans versus total number of scans examined was 96%, this figure being mainly influenced by the high number of true negative scans.